A model for mental health advance directives in the new Victorian Mental Health and Wellbeing Act. Issue 5 (3rd September 2022) - Edan, Vrinda; Maylea, Chris
Abstract : Under the Victorian 2014 Mental Health Act (MHA14), Victorians have a right to advance statements. While there have been initiatives to support uptake, under 3% of consumers have done so. In March 2021, the Royal Commission into Victoria's Mental Health System (the Commission) released its report, including a call to repeal MHA14 and enact a new Act no later than mid-2022. In this paper, we discuss the role of advance planning documentation and instruments used in Australian legislation. Drawing on the Commission's recommendations, models of advance planning in Australia and the Victorian legislative context, this paper proposes a model of both binding and non-binding advance directives. This model would bring the rights of Victorian consumers into alignment with rights provided under the Medical Treatment, Planning and Decisions Act 2016 (Vic) and assist in bringing the new Act into compatibility with the Charter of Human Rights and Responsibilities Act 2006 (Vic).